2005
DOI: 10.19182/remvt.9944
|View full text |Cite
|
Sign up to set email alerts
|

Productivité des brebis Timahdite et croisées D’man x Timahdite en station et chez les éleveurs au Maroc

Abstract: L’étude a porté sur la comparaison des productivités des brebis Timahdite et croisées D’man x Timahdite (DxT) en station et chez quatre éleveurs privés pratiquant le croisement industriel. Ainsi, une dizaine de brebis gravides DxT nées à la station ont été cédées à chaque éleveur. Au total, 131 performances de reproduction des brebis Timahdite et croisées DxT, et 188 performances de croissance et de viabilité des agneaux issus du croisement entre ces brebis et des béliers de race Ile-de-France ont été analysée… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Boujenane and Kansari [6] had reported differences of 0.38 and 0.27 lamb for litter size at birth and at weaning, respectively between ewes of the same genetic groups lambing in the autumn season. Moreover, the superiority of D'man crossbred ewes compared to Timahdite ewes for litter size at birth and at 90 days is consistent with the results of Boujenane et al [5], Boujenane and Kansari [7] and El Fadili et al [10] who found that the difference for litter size between 1/2-D'man and local ewes lambing in the autumn is more than 0.4 lamb.…”
Section: Reproductive Traitssupporting
confidence: 88%
See 1 more Smart Citation
“…Boujenane and Kansari [6] had reported differences of 0.38 and 0.27 lamb for litter size at birth and at weaning, respectively between ewes of the same genetic groups lambing in the autumn season. Moreover, the superiority of D'man crossbred ewes compared to Timahdite ewes for litter size at birth and at 90 days is consistent with the results of Boujenane et al [5], Boujenane and Kansari [7] and El Fadili et al [10] who found that the difference for litter size between 1/2-D'man and local ewes lambing in the autumn is more than 0.4 lamb.…”
Section: Reproductive Traitssupporting
confidence: 88%
“…Its breeding season extends from May to December [12]. D'man crossbred ewes were evaluated during the normal lambing season (November-January) and found to perform better than local breeds [5][6][7]10]. However, it is not known if this superiority is maintained during the other lambing seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Under favorable breeding conditions, this breed reaches a mean post-weaning weight (age at 180 days) of 37.08 ± 5.16 kg (37.71 ± 5.65 kg in the male and 36.38 ± 4.62 kg in the female). The weight at birth of lambs in this breed is largely important compared to other breeds : 3.5 kg in OuledDjellal (IANOR, 2007), 4 kg in Rembi (IANOR, 2013), 3.1 kg in Hamra (IANOR, 2007), 2.60 kg in the D'man breed (Mahouachi et al,2004), 3.7 kg in the Sardi breed (Boujenane et al,2001), 3, 72 kg in the Timahdite breed (Boujenane and Kansari, 2005), 2.8 kg in Ile-de-France (Boujenane, 2005) and comparable to that of the Moroccan breed Boujaâd : 4.95 kg (El Amiri et al, 2010), of the Awassi breed from the Middle East : 4.3 kg (Kridli et al,2006), the Mexican Blackbelly breed : 4.5 kg (Herrera-Alarcón et al,2007). The growth performance achieved by lambs of the Tazegzawt breed is comparable to that of other local breeds in Algeria.…”
Section: Weight and Growth Ability Of Lambsmentioning
confidence: 97%
“…However, the results of this study are well above the mean values reported by Kerfal et al(2005) in the D'man breed : 7.69 kg and 19.8 kg at 30 and 90 days, respectively, by Rekik et al (2008) in the same breed : 3.4 Kg, 5.9 Kg, 11.4 Kg, 13.1 Kg, at 10, 30, 70 and 90 days, respectively, with a ADGs of 100 g/d between the age of 10 and 30 days, by Chikhi and Boujenane (2003) in the Sardi breed, the most important Moroccan breed : 10.9 kg, 22.5 kg and 35.7 kg at 30, 90 and 180 days, respectively with a ADGs of 224 g/d between 0-30 days and 194 g/d between 30 and 90 days and by Boujenane and Kansari (2005) in the Timahditebreed : 9.56 kg and 17.9 kg at 30 days and 70 days respectively.…”
Section: Weight and Growth Ability Of Lambsmentioning
confidence: 99%
See 1 more Smart Citation